Patterns of first-year students use of a university Library: a survey at University of Ibadan (2003)
This paper discusses the mode of use of University of Ibadan Library by first-year students of 2000/2001 academic session. The amount, the nature of use of the library and the barriers between the freshmen and the library are investigated and discussed. The findings reveal that the students heavily use the library to read their own books. The level of borrowing was very low and factors like non- relevance, disorganization of books and lack of basic library use skills were among the major barriers that inhibit the frequent use of the library by the students. Provision of current relevant books, teaching the students’ library use skills through regular lectures and seminars are some recommendations suggested to solve the Problems identified.